Analysis Of Purchasing Halal Certified Pempek Food Products In Muslim Consumer Preferences - Pratiwi, Heni; Hutabarat, Zuhri Saputra; Anggraini, Nadira; Zulfa, Camelia Putri; Setiah, Setiah (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2024)
This research aims to show that halal certification for pempek Furqon food in Jambi City has a positive impact on Muslim consumer preferences. The decision to obtain halal certification reflects a commitment to Islamic halalness, winning the trust of consumers who increasingly prioritize halalness in purchases. Product quality has also proven to be a major factor in influencing consumer preferences, highlighting the need to maintain high quality standards to build and maintain consumer loyalty. In its method, this research applies a qualitative descriptive approach. Interviews and observations were used to collect primary data, focusing on active consumers of Pempek Furqon after obtaining halal certification. Apart from that, the interview subjects also included the management of Pempek Furqon. The results provide significant insight into the factors that influence Muslim consumers' preferences regarding halal products. As a suggestion, Pempek Furqon can continue to improve maintenance of halal certification, strengthen marketing strategies, product innovation and adjust pricing strategies.